(3JaSjQ cJGH OjSbhQjOhSs - (3YHO Gddg Hf CMeO GdeGdbj, VjGA GdOjf, GHf GdHjWGQ , J (B646 (3g` s
(3ChdgG (B:s
(3CeG HYO (B: (3aEfi deG hbaJ ef cJGH GdaGVd OjSbhQjOhS Ydi eG jbUQ Yfg gee LeGYI ef GdeJThajf s
(3BNQgG (B:s
(3hPcQhG Cfg CMO GdLhGgQ GdNeS , aGage Pdc HUQhag jfVM dc eTcdg s
(3TQM ajg CSeGA GdGTLGQ hGdMTGFT hGdGOhjg ef cJGH OjSbhQjOhSs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3JaSjQ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs